Determining Factors In Adoption of Accounting Application - Nurfatimah, Siti Nuke; Rahmawati, Teti; Wiharno, Herma; Yusuf, Fahmi; Darmawan, Erlan (Indonesian Journal Of Business And Economics, 2024)
The study aims to test the determinant MSME players in the adoption of an accounting application in MSMEs. The low intention of MSME players in using the Business Financial Record Application is not in line with the increase in the number of MSMEs every year. This study using Unified Theory of Acceptence and Use of Technology (UTAUT) Model Venkatesh, Morris, Davis, and Davis (2003) with the CIA Security Information Concept (Qadir & Quadri, 2016) to test the intention and use of accounting applications by MSME players. This study uses a combination of the two constructs as previously used in the study Salam and Ali (2020). The sample is 100 respondents, data processing was carried out by testing the validity and reliability and followed by model tests using PLS analysis from the SEM model. The results of the study showed that Performance Expectancy, Perceived Availability, Perceived Confidentialy have an effect on Intention to Use. Meanwhile, the facilitating condition does not affect actual use and Perceived Availability and Perceived Confidentiality also do not affect the intention to use. This study proves that the intention in using accounting recording applications in MSMEs is highly dependent on the environment, both from the community, relatives and even the government. When they start using and get convenience according to their expectations, they tend to continue using the application. The implication of this study is that the phenomenon of low use and adoption of business digital financial applications is one of the tasks for the government, especially in improving the regional economy. By using a digital financial recording application, MSMEs will get a lot of convenience, especially in terms of capital. MSMEs that have strong capital will be able to increase the income of a region.